Readability of Literature Supplied with Plant Protection Chemicals - Basavaprabhu Jirli , Ram Jiyawan , Amit Kumar and Sharada, (Indian Journal of Extension Education, 2013)
Printed materials have been accepted world wide as an important means of communication and have greater significancein the context of increased literacy level over the last few decades. The effectiveness of these printed materials dependslargely on the extent to which they are readable. The present study was undertaken to analyze the readability of literaturesupplied along with plant protection chemicals. The study was conducted in Sevapuri block of Varanasi district of UttarPradesh, because this block has high literacy percentage in comparison to other blocks. Four villages under this blocknamely Maharajpur, Gaharpur, Jaddupur and Bhelupur were selected randomly for the study. A total of 110 farmers whogrew varieties of cereals and vegetables and used Plant Protection Chemicals (PPCs) for protecting their crops from theincidence of insect-pests and diseases were the respondents of the study. The findings of the study revealed that majorityof the farmers had completed their higher secondary education (61%). Further all the farmers said that they were awareabout literature supplied with PPCs, but only 37 per cent of them read the literature. All the farmers agreed that too manytechnical words used, font size used, poor paper quality, lack of illustration and difficult to understand the applicationmethods regarding PPCs suggested in the literature considered as main constraints in reading the literature. Hencereadability constraints should be eliminated and farmers should be encouraged to read and follow the instructionsmentioned in the literature.